Legal Protection for Workers during the Spread of COVID-19 in the United Arab Emirates (UAE) - Ahmed Alshamsi; Mohd Zakhiri Md Nor; Muhamad Noor Habibi Hj Long (International Journal of Latin Notary, 2023)
Since the beginning of the pandemic COVID-19 that hit the world in December 2019, most countries of the world have passed legislation and measures that vary according to their need and nature. This research paper studies legal legislation passed in the UAE to protect workers from losing their source of livelihood while carrying out precautionary measures in the fight against the coronavirus and its continuous mutation. This paper adopted qualitative research method. The data be analysed by using thematic and content analysis method.This paper concludes that there are adequate legal protection for workers during the Spread of Covid-19 in the United Arab Emirates (UAE).